1348 Exploring differences in brain perfusion using arterial spin labelling in patients with childhood craniopharyngioma. (17th August 2022) - Naeem, Nimra; Elsworth, Rebecca; Narayan, Kruthika; Lithander, Fiona; Elson, Ruth; Taylor-Miller, Tashunka; Wilson, Aileen; Hamilton-Shield, Julian; Crowne, Elizabeth; Hinton, Elanor
Abstract : Aims: Craniopharyngioma (CP) is a rare and benign suprasellar tumour with significant long-term sequel like obesity. There is poor understanding around the pathophysiology underpinning this weight gain, which may be linked to hypothalamic damage. One of the aims of this pilot, feasibility study was to investigate the downstream effect of CP on brain perfusion by using arterial spin labelling (ASL) as an indirect measure of neural metabolic activity in young people with CP. Methods: Nine participants with CP (mean age= 14.6 ± 3.8y; mean BMI SDS= 0.97 ± 1.93) and nine sex matched controls (mean age= 22.4 ± 2.6y; mean BMI SDS= -0.60 ± 0.88) underwent two fasted, functional magnetic resonance imaging scans: one high resolution structural T1- weighted scan and one pseudo-Continuous ASL scan (pCASL) with multiple post-labelling delays. Data was processed with BASIL and analysed with RANDOMISE. Correlations between BMI SDS and brain perfusion were processed using Kendall's tau analysis. Results: Preliminary evidence shows greater perfusion in six of the seven priori regions of interest (ROI) (hypothalamus, insula, amygdala, nucleus accumbens, putamen and ventrofrontal cortex) in the control group compared to the CP participants (p<0.01). No difference was found in the temporal occipital fusiform cortex: the only ROI not associated with food reward processing. No significant correlations (p<0.01) were found between BMI SDS and brain perfusion in the above regions within the two groups. Conclusion: These preliminary findings suggest there is reduced neural metabolic activity within and beyond the hypothalamus in those with CP. This is a shift from current literature which focuses primarily on the role of the hypothalamus. The findings have implications for the role of food reward processing within the pathophysiology behind CP-related obesity. There is need for further analysis to contextualise these results to determine this relationship with eating behaviour and obesity.